Emulsion-mediated synthesis of hierarchical mesoporous-macroporous Al-Mg hydrotalcites - Petrolini, Davi D. [UNESP]; Urquieta-González, Ernesto A.; Pulcinelli, Sandra H. [UNESP]; Santilli, Celso V. [UNESP]; Martins, Leandro [UNESP] (Elsevier, 2017)
A new sol-gel method mediated by the use of paraffin emulsions is presented for the synthesis of hierarchical mesoporous-macroporous Al-Mg hydrotalcites. Prior to the synthesis, the construction of ternary diagrams for paraffin/surfactant/ethanol helped to identify the most suitable compositional synthesis domain. Two distinct regions, denoted L1 (transparent microemulsion) and L2 (opaque emulsion) were identified for low and high concentrations of paraffins, respectively. The ternary diagrams revealed some features: i) n-hexane (C6) had the smallest L2 region; ii) the high viscosity of n-octadecane (C18) did not allow control of phase separation, and iii) the most suitable paraffin for the use as the emulsifier was the intermediate-sized n-dodecane (C12). The use of paraffin in concentrations included in the L1 region did not contribute to the creation of pores, but the emulsion templating in the L2 region led to hierarchical porous hydrotalcites when were calcined up to 250 °C having enhanced textural properties and presenting mesopores and macropores with mean sizes of 0.02 and 1 μm, respectively. The slit-like shaped mesopores were caused by the partial exfoliation of hydrotalcite layers unordered packed around the emulsion droplets, while the macropores arose from voids left by the droplets after thermal treatment. The singular textural properties of the studied Al-Mg hierarchical porous hydrotalcites turns the emulsion mediated-synthesis a potential method to obtain more efficient catalysts to be used in process involving bulky molecules.
Keywords: Hierarchical porous structure; Hydrotalcites; Paraffin-surfactant emulsion; Sol-gel synthesis